Residual tumour hypoxia in head-and-neck cancer patients undergoing primary radiochemotherapy, final results of a prospective trial on repeat FMISO-PET imaging. Issue 3 (September 2017) - Löck, Steffen; Perrin, Rosalind; Seidlitz, Annekatrin; Bandurska-Luque, Anna; Zschaeck, Sebastian; Zöphel, Klaus; Krause, Mechthild; Steinbach, Jörg; Kotzerke, Jörg; Zips, Daniel; Troost, Esther G.C.; Baumann, Michael
Abstract: Background: Hypoxia is a well recognised parameter of tumour resistance to radiotherapy, a number of anticancer drugs and potentially immunotherapy. In a previously published exploration cohort of 25 head and neck squamous cell carcinoma (HNSCC) patients on [ 18 F]fluoromisonidazole positron emission tomography (FMISO-PET) we identified residual tumour hypoxia during radiochemotherapy, not before start of treatment, as the driving mechanism of hypoxia-mediated therapy resistance. Several quantitative FMISO-PET parameters were identified as potential prognostic biomarkers. Here we present the results of the prospective validation cohort, and the overall results of the study. Methods: FMISO-PET/CT images of further 25 HNSCC patients were acquired at four time-points before and during radiochemotherapy (RCHT). Peak standardised uptake value, tumour-to-background ratio, and hypoxic volume were analysed. The impact of the potential prognostic parameters on loco-regional tumour control (LRC) was validated by the concordance index (ci) using univariable and multivariable Cox models based on the exploration cohort. Log-rank tests were employed to compare the endpoint between risk groups. Results: The two cohorts differed significantly in several baseline parameters, e.g., tumour volume, hypoxic volume, HPV status, and intercurrent death. Validation was successful for several FMISO-PET parameters and showed the highest performance (ci = 0.77–0.81) after weeks 1 and 2 of treatment. Cut-off values for the FMISO-PET parameters could be validated after week 2 of RCHT. Median values for the residual hypoxic volume, defined as the ratio of the hypoxic volume in week 2 of RCHT and at baseline, stratified patients into groups of significantly different LRC when applied to the respective other cohort. Conclusion: Our study validates that residual tumour hypoxia during radiochemotherapy is a major driver of therapy resistance of HNSCC, and that hypoxia after the second week of treatment measured by FMISO-PET may serve as biomarker for selection of patients at high risk of loco-regional recurrence after state-of-the art radiochemotherapy.